The Influence of Transactional Leadership Style on Employee Turnover Intention at Cool Supermarket Tomohon - Yoas Sotomo Telaumbanua; Deetje Josephine Solang; Rinna Yuanita Kasenda (Cita konsultindo, 2026)
Turnover intention is an important aspect of human resource management because it is associated with employees' tendency to leave an organization. One factor that is presumed to influence turnover intention is transactional leadership, which emphasizes an exchange relationship between leaders and subordinates through the provision of rewards and performance monitoring. This study aimed to examine the effect of transactional leadership on the turnover intention of employees at Cool Supermarket Tomohon. This research employed a quantitative approach with an associative research design. The study population consisted of 55 employees, all of whom were selected as the sample using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using normality, linearity, and simple linear regression tests with the assistance of IBM SPSS Statistics 25.0. The results indicated that transactional leadership had a negative and significant effect on turnover intention, with a regression coefficient of -0.901 and a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) was 0.936, indicating that 93.6% of the variation in turnover intention was explained by transactional leadership, while the remaining 6.4% was influenced by other factors outside the scope of this study. These findings suggest that the better the implementation of transactional leadership, the lower the employees' turnover intention.